1977
DOI: 10.1073/pnas.74.4.1445
|View full text |Cite
|
Sign up to set email alerts
|

Partial reaction of peptide initiation inhibited by phosphorylation of either initiation factor eIF-2 or 40S ribosomal proteins.

Abstract: Preparations of the hemin-controlled repressor (HCR) from rabbit reticulocytes contain 3':5'-cyclic-AMP-independent protein kinase activity for the smallest subunit of the peptide initiation factor eIF-2 and for proteins of reticulocyte 40S ribosomal subunits. Binding of the ternary complex formed between Met-tRNAf, GTP, and eIF-2 to 40S ribosomal subunits is shown to be inhibited by phosphorylation of either the ribosomal subunits or eIF-2. The protein kinase activity responsible for phosphorylation of eIF-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Gross and The publication costs of this article were defrayed in part by page charge payment. This article must therefore be hereby marked "advertisement" in accordance with 18 Fractionated Protein-Synthesizing System Assay. The fractionated cell-free system was that described by Hardesty et al (14).…”
mentioning
confidence: 99%
“…Gross and The publication costs of this article were defrayed in part by page charge payment. This article must therefore be hereby marked "advertisement" in accordance with 18 Fractionated Protein-Synthesizing System Assay. The fractionated cell-free system was that described by Hardesty et al (14).…”
mentioning
confidence: 99%
“…The inhibitor has been identified as a cyclic AMPindependent protein kinase that specifically phosphorylates the 38,000-dalton polypeptide (a subunit) of eIF-2 (21)(22)(23)(24)(25). This phosphorylation of eIF-2 prevents the binding of Met-tRNAf to the 40S ribosomal subunit in crude and in partially purified systems (24,(26)(27)(28). Recent evidence indicates that the formation of the ternary complex [eIF-2-Met-tRNAf-GTP] and its subsequent binding to 40S subunits may involve other factors in addition to eIF-2 (29)(30)(31)(32) and that the phosphorylation of eIF-2 may inhibit its interaction with these factors (28,32).…”
mentioning
confidence: 99%
“…Inhibition may be dependent on the simultaneous phosphorylation of P55 and eIF-2a. Kramer et al [45] have suggested that the phosphorylation of both eIF-2a and 40-S ribosomal subunits is required for inhibition; however, this is unlikely since no increased phosphorylation of ribosomal proteins was observed in these studies.…”
Section: Discussionmentioning
confidence: 50%